1999
DOI: 10.1046/j.1365-2036.1999.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Rectal and colonic mesalazine concentration in ulcerative colitis: oral vs. oral plus topical treatment

Abstract: Topical treatment of mesalazine significantly increases mucosal concentrations of mesalazine up to the splenic flexure, supporting the rationale to treat left-sided ulcerative colitis with topical formulations of mesalazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 21 publications
2
58
0
1
Order By: Relevance
“…In recent years, both in vitro and in vivo studies have shown that mesalamine inhibits multiple biological pathways that sustain colon cancer cell growth, thereby reducing the risk of developing inflammatory bowel disease-related colon cancer (20)(21)(22). However, the antineoplastic effects of mesalamine are seen only with doses that are not always reached in the gut following oral administration of the drug (23,24). Therefore, we developed several derivatives of mesalamine and selected 2-14 as it was the more potent inhibitor of colon cancer cell growth (25).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, both in vitro and in vivo studies have shown that mesalamine inhibits multiple biological pathways that sustain colon cancer cell growth, thereby reducing the risk of developing inflammatory bowel disease-related colon cancer (20)(21)(22). However, the antineoplastic effects of mesalamine are seen only with doses that are not always reached in the gut following oral administration of the drug (23,24). Therefore, we developed several derivatives of mesalamine and selected 2-14 as it was the more potent inhibitor of colon cancer cell growth (25).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, attenuation of p-EGFR is obtained with 5-ASA concentrations, which are reached within the gut tissue under standard oral treatment. 21,22 The effect of 5-ASA on p-EGFR is reversible and associates with no induction of cell death. In contrast to our data, two different groups have recently shown that 5-ASA promotes apoptosis of adherent HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, CRC cell lines were either left untreated or treated with physiological doses of 5-ASA, and then p-EGFR assessed by Western blotting. Immunoblot analysis of lysates of CRC cells showed a dramatic reduction in the constitutive level of p-EGFR after culture with physiological concentrations of 5-ASA (Figure 1a), 21,22 and this was evident in each of the four CRC cell lines used (not shown).…”
Section: -Asa Inhibits the Activation Of Egfr In Colon Cancer Cellsmentioning
confidence: 96%
“…[13][14][15][16] The addition of topical 5-ASA to oral therapy increases mucosal levels of mesalamine by 3-fold in the descending colon and over 20-fold in the rectum. [17] Moreover, it has been demonstrated repeatedly that the combination of 5-ASA in oral and enema formulations is superior to either therapy alone in inducing and maintaining remission of extensive colitis. [13][14][15][16][17][18] Safety of 5-ASA Therapy:-As a class, 5-ASA therapy is considered exceptionally safe.…”
Section: Induction Of Remission In Ulcerative Colitismentioning
confidence: 99%
“…[17] Moreover, it has been demonstrated repeatedly that the combination of 5-ASA in oral and enema formulations is superior to either therapy alone in inducing and maintaining remission of extensive colitis. [13][14][15][16][17][18] Safety of 5-ASA Therapy:-As a class, 5-ASA therapy is considered exceptionally safe. The side-effect profiles of mesalamine and balsalazide are similar to placebo, whereas olsalazine and sulfasalazine are associated with an increased incidence of treatment withdrawal due to adverse events.…”
Section: Induction Of Remission In Ulcerative Colitismentioning
confidence: 99%